TiO2 inverse opal by ALD for solar cell application - Tan, Jacqualine Yan Ling. (2009)
The focus of this project is on the usage of Atomic layer deposition (ALD) methods to create a type of 3D photonic crystals (PhCs) in particular inverse opal that has suitable photonic band gap in the visible light spectrum. Titania (TiO2) is one of the promising materials to create inverse opals structures or 3D photonic crystals structure due to it high refractive index (n) This is especially so in the anatase and rutile phase. Making use of the dielectric contrast between TiO2 and air pores in inverse opals structure. The inverse opals can be manipulated to increase the absorption efficiency in the solar spectrum. Titania (TiO2) thin films were studied to indicate the relationship of growth temperature with respect to growth rate, surface roughness and crystallinity. Thin films were also act as a preliminary platform to optimize the parameter for applying those parameters to opals infiltration. Thin film characterization indicates that increasing temperature will result in a decrease in rate of growth for every cycle. A low growth temperature will give rise to a low surface roughness which is exceptionally important for solar application. Thin films are then heat treated to convert the deposited film from amorphous to anatase phase. This is to improve the refractive index properties of TiO2. After the parameters for thin film deposition were optimized, these parameters were applied to opals infiltration. During infiltration, both the hold and purge time were lengthen to improve the filling fraction. Currently, only 12.4% of TiO2 are able to infiltrate into the pores. It was believe that the filling fraction could be improved by carrying out focus- ion beam (FIB) to remove the defects on the surface of the opals before infiltration.